Sam & Dave dig a hole [book with audioplayer] - Barnett, Mac ([Library Ideas, LLC], 2019)
Sam and Dave are on a mission. A mission to find something spectacular. So they dig a hole. And they keep digging. And they find ... nothing. Yet the day turns out to be pretty spectacular after all.